2019
DOI: 10.1002/ejoc.201900499
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Spirooxindole Oxetanes Through a Domino Reaction of 3‐Hydroxyoxindoles and Phenyl Vinyl Selenone

Abstract: An unprecedented Michael/intramolecular etherification cascade reaction of phenyl vinyl selenone with 3‐hydroxyoxindoles under aqueous basic conditions at room temperature is described. The method provides a domino access to new spirooxindole 2,2‐disubstituted oxetanes in moderate to good yields under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…At this purpose, a few years ago, we reported the stereoselective synthesis of tetrahydrofuran-3-ols by means of a tin-mediated radical cyclization of 5-phenylseleno-3-oxa-pentanals (Scheme 1, path c) [14]. As a continuation of this work,and part of our studies in the use of selenium reagents for the synthesis of heterocycles of biological interest [15][16][17][18], we now report our attempts to construct pyrrolidin-3-ols using 5-phenylseleno-3-aza-pentanals as radical precursors (Scheme 1, path d). 3-Hydroxylated pyrrolidines were identified in several natural products and compounds of pharmaceutical interest.…”
Section: Introductionmentioning
confidence: 92%
“…At this purpose, a few years ago, we reported the stereoselective synthesis of tetrahydrofuran-3-ols by means of a tin-mediated radical cyclization of 5-phenylseleno-3-oxa-pentanals (Scheme 1, path c) [14]. As a continuation of this work,and part of our studies in the use of selenium reagents for the synthesis of heterocycles of biological interest [15][16][17][18], we now report our attempts to construct pyrrolidin-3-ols using 5-phenylseleno-3-aza-pentanals as radical precursors (Scheme 1, path d). 3-Hydroxylated pyrrolidines were identified in several natural products and compounds of pharmaceutical interest.…”
Section: Introductionmentioning
confidence: 92%
“…107 In 2019, Marini reported a domino reaction of 3-hydroxyindoles and phenyl vinyl selenone. 108 Using KOH in aqueous conditions Marini showed that protected or unprotected isatins could be used to produce a variety of 3,2′-spirooxetanes in 34-73% yield. Lindsley synthesised 3,3′-spirooxetane 24 from the corresponding isatin in 3 steps in an SAR study to find a sub micromolar and selective M 5 (muscarinic acetylcholine receptor 5) positive allosteric modulator for the treatment of a variety of neurological diseases.…”
Section: Spirooxetanyl Oxindolesmentioning
confidence: 99%
“…In this telescopic protocol, the 1-alkyl-3-phenylseleno-2-propen-1-ols were oxidized with m-CPBA and then treated with NaOH in MeOH. The methoxide ion adds to vinyl selenones generating oxa-Michael adducts that after proton transfer and intramolecular nucleophilic substitution gave methoxyoxetanes in good yields, as 2:1 mixtures of Aqueous basic conditions were also successfully employed for the construction of a challenging spiro 2,2-substituted oxetane motif in moderate to good yields [27]. The Michael addition/intramolecular etherification cascade was performed with N-protected or unprotected 3-hydroxy isatins and the phenyl vinyl selenone without addition of surfactants (Scheme 5).…”
Section: Scheme 2 Cyclopropanations Of Active Methylene Compounds With Vinyl Selenonesmentioning
confidence: 99%